A predictive analytical model of thermal conductivity for aluminum/transition metal high-entropy alloys. (1st February 2022) - Abere, Michael J.; Ziade, Elbara; Lu, Ping; Saltonstall, Christopher B.; Gu, Xiaojun; Wright, Wendelin J.; Argibay, Nicolas; Kustas, Andrew B.
Abstract: A predictive analytical model for the thermal conductivity of Aluminum/transition metal based high-entropy alloys based on contributions from the electron and lattice subsystems is presented. Lattice conductivity is modeled as an oscillator damped by electron-phonon and defect scattering. Electron subsystem conductivity is dominated by scattering from the aperiodic crystal potential arising from alloying atom induced lattice disorder; its effect was quantitatively calculated using a virtual crystal approximation. We show that model predictions agree with published values and for an exemplar high-entropy alloy largely based on transition (i.e., non-refractory) elements, Alx CoCrCuy FeNi. Within this alloy system, the crystal structure varies between face centered cubic and body centered cubic depending on composition and temperature, and it was found that thermal conductivity behaves as a weighted-average composite of the multiple phases. Graphical abstract: Image, graphical abstract